The Theology of a Jealous God: A Study of Exodus 20:3-5 and a Jealous God - Brian Marpay; Nasokhili Giawa (Sekolah Tinggi Teologi Simpson, 2021)
Jealousy is one of the characteristics of God, which is essential in His divinity. It's just that some take it casually and even tend to see that jealousy like this is not too severe. This is why this article was written to ascertain the extent to which God's jealousy is essential to be studied by God's people and its application from the perspective of the responsibility of faith in Him. It should be understood that the Bible shows this nature of God, that He is a jealous God. However, this jealousy of God is certainly not as heavy as humans' jealousy in general. God was jealous of the acts of disloyalty made by humans against Him, namely deliberately rebelling against and worshiping other gods. God has the right to be jealous because of the disobedience of His chosen people, who have violated the content of His eternal covenant. Therefore, this article is written using a biblical-theological approach, namely trying to understand the purpose of God's jealousy as contained in Exodus 20: 3-5 by paying attention to the text and context and then analyzing it to find its value, relevance, and application in daily life. In the end, this article shows that the background behind God's jealousy is, firstly, there is a broken promise, second is the existence of a double attitude (because of a special relationship before), and the third is that there is an attitude of relationship dissatisfaction that causes jealousy, namely adultery with other gods. ABSTRAKSikap cemburu merupakan salah satu sifat khas Allah yang esensial dalam keilahian-Nya. Hanya saja, ada yang menanggapinya secara biasa saja bahkan cenderung melihat bahwa sifat cemburu seperti ini tidak terlalu serius. Inilah yang menyebabkan artikel ini ditulis untuk memastikan sejauh mana kecemburuan Tuhan penting dipelajari oleh umat Tuhan dan aplikasinya dari perspektif tanggung jawab iman kepada-Nya. Perlu dipahami bahwa Alkitab menunjukkan sifat Allah ini, bahwa Ia adalah Allah yang cemburu. Namun, kecemburuan Allah ini tentu tidak sama bobotnya dengan kecemburuan yang biasa dilakukan manusia pada umumnya. Sejujurnya Tuhan Allah sangat cemburu dengan tindakan ketidaksetiaan yang dibuat oleh manusia terhadap-Nya yaitu dengan sengaja memberontak dan menyembah allah lain. Allah berhak cemburu karena ketidak-taatan umat pilihan-Nya yang telah melanggar konten kovenan-Nya yang kekal. Karena itu, artikel ini ditulis menggunakan pendekatan teologi biblika yaitu berupaya memahami maksud kecemburuan Allah sebagaimana dimuat di dalam Kel. 20:3-5 dengan memperhatikan teks dan konteks lalu menganalisis untuk menemukan nilai, relevansi, dan aplikasinya dalam kehidupan sehari-hari. Pada akhirnya artikel ini memperlihatkan bahwa yang menjadi latar belakang di balik kecemburuan Allah ialah, pertama adanya janji yang diingkari, kedua ialah adanya sebuah sikap menduakan (karena adanya hubungan spesial sebelumnya), dan yang ketiga ialah adanya sikap ketidakpuasan relasi yang menimbulkan kecemburuan yaitu perzinahan dengan allah-allah lain.